Fluency: Deep Roots in Reading Instruction - William H. Rupley; William Dee Nichols; Timothy V. Rasinski; David Paige (Education Sciences, 2020)
Over the past two decades, reading fluency has been increasingly recognized as an important instructional variable for success in reading. Yet, this has not always been the case. This article presents a historical review of the nature and role of fluency instruction in the United States. The roots of oral reading fluency began in an age when texts and other forms of entertainment and information were limited. Historically, in America, oral reading was the predominant means for conveying ideas and passing the time at home with the family. In the 1800s, American education’s primary method of instruction emphasized the need for being able to read aloud with expression and fluency, in order to hold the listeners’ attention and convey information. As texts and other forms of information became more available, oral reading became deemphasized, and silent reading was viewed as a better approach to developing readers’ comprehension at the cost of fluency development. With continued research and national reports that indicate the significant contributions of oral reading fluency to reading comprehension and academic proficiency, it is clear that the roots of oral reading run deep, and that fluent reading development is important to learners’ academic achievement and reading comprehension.